2006
DOI: 10.1111/j.1365-246x.2006.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on mantle anelasticity from geodetic observations, and implications for theJ2anomaly

Abstract: S U M M A R YWe use geodetic observations of the Earth to constrain anelasticity in the Earth's mantle at periods between 12 hr and 18.6 yr. The observations include satellite laser ranging (SLR) measurements of 12 hr and 18.6 yr tides in the J 2 component of the gravity field; spacebased observations of tidal variations in the Earth's rotation rate; and optical and space-based measurements of the Chandler Wobble period and damping. These geophysical signals are mostly sensitive to the lower mantle. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
134
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(148 citation statements)
references
References 35 publications
14
134
0
Order By: Relevance
“…4a). And it does an even better job than the Benjamin et al (2006) model of increasing the coherence with AAM and OAM (compare Figs. 3d and 4b).…”
Section: Inelasticmentioning
confidence: 94%
See 4 more Smart Citations
“…4a). And it does an even better job than the Benjamin et al (2006) model of increasing the coherence with AAM and OAM (compare Figs. 3d and 4b).…”
Section: Inelasticmentioning
confidence: 94%
“…3c and d shows the results of removing the fortnightly and monthly ocean tide model preferred by Benjamin et al (2006) from length-of-day observations that have also had elastic and inelastic body tidal, atmospheric, and non-tidal oceanic effects removed. As can be seen, the Benjamin et al (2006) model does an excellent job of accounting for the observed power at the fortnightly and monthly tidal frequencies (Fig. 3c).…”
Section: Inelasticmentioning
confidence: 97%
See 3 more Smart Citations